Enhancing Eco-Facilitator Competencies through Interactive E-Workbook Development: A Study Using the ADDIE Model - Sri Kuswantono Wongsonadi; Hikmah Hikmah; Retno Dwi Lestari; Nararia Hutama Putra (Publikasi Indonesia, 2025)
This study evaluates the effectiveness of an interactive e-workbook designed to enhance the competencies of eco-facilitators in environmental education. Using a pretest-posttest design, we assessed improvements in key competencies, including facilitating sustainable behaviors, practical environmental skills, and theoretical knowledge. The results show significant increases in posttest scores across all measured domains, with the greatest gains observed in facilitating eco-friendly learning activities and designing sustainable projects. Statistical analyses, including paired t-tests and Cohen’s d, confirmed a substantial impact, with an effect size of 39.63, highlighting the e-workbook's practical significance in skill enhancement. User satisfaction and usability assessments revealed high engagement with the content and functional accessibility, though minor areas for improvement were identified. These findings underscore the potential of interactive e-learning tools in supporting eco-facilitators to promote environmental literacy and sustainable practices. This research provides valuable insights into digital education strategies for environmental professionals and suggests opportunities for further refinement and broader application in diverse educational settings.